(3cJGH GdNdhIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3cGJH GdGeQ GdeMche GdeQHhW s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Cdge GdUahI ef YHGOg CJNGP GdNdhGJ CeG HYO aEfc SCdJ CjgG Gdehdi GdYGQa YQac Gddg eGdGfgGjI dg ef GdeYGQa Gf CbjO dc UhQ GdGSJYOGO GdLGeY Gdcdi GdPi dGjJbjO HGSe s
(3BNQgG (B:s
(3hEPG ageJ cjajI MGdGJ GdNdhg hUhQJgG aGONdgG HCi PcQ TFJ aEfg jYWjc eG ai bhJg hdGHO hjcai gPG GdbOQ ef GdJfHjg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1416s
Keywords: (3GdJUha hGdBOGH GdTQYjIs